Analysis of Conformity of Land Use of River Basin Area in Kelurahan Sungai Jingah Based on Applicable Government Regulation - Andi Mahreda; Chika P. Rahali; Maulidah Maulidah; Nazarullah Amin (Green Visioneers, 2018)
The river is the most important thing for human life, one component of the environment especially for who lives in the city. Changes in the function of some or all of the land area of its original function is a problem that develops today, one of which land transfer function in the river border. The river border is the left and right crosses of the riverbed defined as a protection boundary. The existence of regulations that regulate the river banks, making the river bank area martapura Sungai Kelurahan Jingah a place of research. This study aims to identify and analyze the suitability of land use along the river banks Martapura Sungai Jingah River with the applicable regulations.